Age-Group Differences and Annual Variation in Return-To-Play Practices After Sport-Related Concussion. Issue 1 (January 2022) - Kerschner, Anna E.; Huber, Daniel L.; Brett, Benjamin L.; Meier, Timothy B.; Nelson, Lindsay D.; McCrea, Michael A.
Abstract : Objective: To examine return-to-play (RTP) practice differences between high school and collegiate athletes, as well as the stability (ie, year-by-year) in these practices over a 5-year period. We hypothesized that similar protocols for treatment will be comparable across competition levels and that these practices will vary year-to-year. Design: Prospective cohort study. Setting: Nine high schools and 4 National Collegiate Athletic Association Division III colleges in Southeastern Wisconsin. Participants and Independent Variables: Two-hundred seventy-three (N = 273) athletes with sport-related concussions (SRCs). Independent predictors included competition level (high school, n = 88 vs collegiate, n = 185) and year-of-injury. Outcome Measures: Athletes were evaluated prospectively for differences in symptom duration, symptom free waiting period (SFWP), and time to RTP, as well as longitudinal changes in management. Results: High school and collegiate athletes experienced comparable median symptom duration (high school, 6.0 days, interquartile range (IQR) = 3.5-11.0; college, 6.0 days, IQR = 4.0-9.0, P = 0.95), SFWP (high school, 5.0 days, IQR = 3.0-8.0; college, 5.0 days, IQR = 3.0-7.0, P = 0.12), and total time to RTP (high school, 10.5 days, IQR = 7.0-16.0; college, 11.0 days, IQR = 8.0-14.0 days, P = 0.94). A Cox regression analysis revealed a nonsignificant trend toward longer SFWPs in high school athletes ( P = 0.055; hazard ratio = 1.347, confidence interval = 0.99-1.83). Among football players, SFWPs in 2017 (Median = 3.5 days, IQR = 1.5-5.0 days) were significantly longer than those in 2014 (Median = 5.0 days, IQR = 4.0-8.5 days, P = 0.029) after correction for multiple comparisons. Conclusion: Similar postinjury and RTP management practices were observed at the high school and collegiate levels after SRCs. Symptom duration and time from injury to unrestricted RTP were comparable, although high school athletes may have longer SFWPs.